The Assessment Of Social-Ecological Landscape And Tsunami Disaster Resilience On Bustanus Salatin City Park In Banda Aceh - Era Nopera Rauzi (Faculty of Engineering, Malikussaleh University, 2018)
Bustanus Salatin or Taman Sari Aceh was one of the largest public open space more than twenty years ago. However, after more than one decade tsunami hit Banda Aceh, the park changed and got more amenities to support public activities inside. This research aims to assess function, quality of space, and activities whether it is related to socialecological and resilience of tsunami disaster. The methodology in this research were field survey, zone mapping and digital measurement. The findings of field survey were permanent buildings with different heights almost covered seventy five percent of park area. Overall physical conditions were not well maintained so the existing facilities become redundant and not well functioned. Furthermore, playground area was diminished because of new adding stage in the middle of park which influence social-ecology landscape and public activities. Moreover, the highest building should be evacuation space for resilience of tsunami disaster.